Studying the Human Scale and Proportionality of Great Mosque in Jawa Timur, Indonesia - Hammam Rofiqi Agustapraja; Izudinshah Bin Abd Wahab (Journal of Islamic Architecture, 2023)
The proportion and scale of humans in the building are one of the invoices in shaping the beauty and effectiveness of the function of the building. In architecture, there is a golden ratio as a reference for calculating the proportions of a shape. While in Indonesia, especially in Java and Bali, there is a traditional measurement method for developing a building, using body anatomy measurements. This study uses the Golden Ratio and Traditional Measurement methods to analyze the dimensions of the prayer room at the Great Mosque in East Java with case studies of the Lamongan Great Mosque, Tuban Great Mosque, and Gresik Jamee Mosque. The results obtained from this study for the dimensions of the existing prayer room with the largest percentage approaching the golden ratio are the prayer room of the Great Mosque of Lamongan (82%), and the smallest is the Jami Gresik Mosque (61.8%). While the dimensions of the prayer room need adjustments to be more effective in meeting the human scale in performing prayers, traditional measurement methods that approach modern measurements use "kilan" and "hasta." From these results, it is hoped that in the future, mosque planning can pay attention to the proportions and dimensions of the human scale, both with modern and traditional measurements, which are the local wisdom of the local culture.